Дослідження реологічних властивостей дріжджового тіста протягом ферментації - Попова, Світлана Юріївна; Слащева, Аліна В’ячеславівна (НТУ "ХПІ", 2016)
У роботі доведена перспективність використання сухої картопляної добавки (СКД) із вторинних продуктів переробки картоплі (ВППК) в технологіях виробів із дріжджового тіста. Встановлено, що використання СКД поліпшує фізичні та структурно-механічні властивості дріжджового тіста під час розстоювання. Досліджено вплив добавки на зміни напруження зсуву та в’язкості зразків тіста із додаванням СКД залежно від тривалості розстоювання та сорту борошна. Встановлено, що зміни в’язкості однакові як для контрольних зразків тіста з борошна обох досліджуваний партій, так і з додаванням СКД, що свідчить про можливість використання добавки різної концентрації без суттєвих змін структурно-механічних властивостей тіста.

The purpose of the research was the substantiation of rational concentration of dry potato supplements from the point of view of the rheological properties of dough. Studies conducted in model systems yeast dough obtained by the accelerated method. Express technology due to pre -activation of yeast (Saccharomyces cerevisia is) in a nutrient medium consisting of water and dry additives from the secondary products of processing of potatoes. The study on the determination of the viscosity and shear stress of the dough depending on the concentration of the dry addit ive and potato flours. The results of experimental studies of all samples showed that they possess stable structure, which destr uction begins only after reaching a certain voltage. Therefore, the investigated test specimen with dry potato Supplement have a stable str ucture, which ensures that no sticking of the dough on the working bodies of technological equipment and promotes eff iciency. It is proved that the use of a dry potato additives in a concentration of 5 % by weight of flour contributes to dough with a stable rheological performance. The obtained results can be used in the baking industry with the aim of intensification of the process of production of yeast dough.
The study of rheological properties of dough during fermentation
Keywords: хлібопекарське виробництво; переробка картоплі; вторинні продукти; суха картопляна добавка; структурно- механічні властивості; secondary products; processing of potatoes; potato dry additive; structural and mechanical properties; yeast dough